The total quality services and business productivity of receptive turism in Miraflores, 2019 - Huayta Bautista, Sara Susana (2021)
Objective: This study aims to determine the relationship between service quality and business’ productivity of receptive tourism travel agencies in Miraflores (Lima, Peru), during the period of 2019. Method: The research was applied and empirical, has a non-experimental cross-sectional correlation, with a quantitative approach. The sample was made up of 50 tourist service providers from different travel agencies located in Miraflores district. Results: The results of the research show a strong and positive association of variables and dimensions. From a total of 50 tourist providers; 23 of the surveyed, which represents a 46%, stated the existence of a very good relationship between the variables of service quality and business’ productivity. Conclusion: The results indicate that the level of the travel agencies’ service quality has greatly decreased due to factors such as informality and the low percentage (9.7%) of travel agencies that have good practice application systems or quality management systems. Therefore, the study aims to improve the tourist agencies’ competitiveness and exceed the demands of the global market.